EDUCATION AND INEQUALITY OF THE POPULATION: RELATIONSHIPS AND CONTRADICTIONS - Putytskyi, Anton (Socio-economic relations in the digital society, 2023)
In the theory of human capital, education (as well as health) is the main object of investment, which ensures an increase in labour productivity, and therefore, an increase in the volume of goods and services, on the one hand, and an increase in the income of a working person, on the other. This article continues the research of leading Ukrainian and foreign scientists to identify the main trends that determine the impact of education on population inequality.The main purpose of the article is to outline and substantiate the interrelationships and contradictions between education and inequality. For this, educational inequality was considered as inequality of access to education, inequality of access to quality education, inequality of educational chances or opportunities, inequality of educational standard, and inequality of educational results. In this context, it is determined that a significant factor influencing inequality is the dominance of instructions for obtaining higher education and the competitiveness of educated persons in the labour market. As a result of the conducted analysis, it was established that the presence of higher education not only significantly reduces the risk of poverty and increases the probability of obtaining average incomes but also significantly affects the way of life, in particular, consumer behaviour. Quality education is one of the main factors of financial security. Significantly higher monetary incomes of educated people force the latter to resort to such types of economic activity as work in a personal subsidiary economy less. The conducted analysis makes it possible to state that a higher level of education of at least one member of the household, and especially its head, is a guarantee of a lower risk of poverty. Thus, education today can be defined as the most effective and promising factor in reducing the risk of family poverty. The article proves that public investment in the education of their children is recognized as the most promising and profitable investment in their future. The study of the phenomenon of educational migration showed that it brings much more advantages to the recipient countries than to the donor countries, and therefore the inequality of the population in the donor countries will always be higher than in the recipient countries.
Keywords: education; population inequality; education of the population; educational migration; transformation of education; human capital; inequality in access to higher education